LabVIEW use in modeling and performance test bit error rate of a communication system with high order QAM modulation 2 4 1 and coding Reed-Solomon for undergraduate teaching - Meléndez Pertuz, Farid; Vélez Diaz, Juan Carlos; Caicedo Ortíz, José; Fernández Vélez, Alfredo (Rev. Téc. Fac. Ing. Univ. Zulia, 2017)
To show the ease of use of the programming environment of LabVIEW in the teaching of telecommunications at the undergraduate level, it is implemented and simulates a system of modern communications using QAM modulation of higher order and coding Reed-Solomon shortened version (204,188, t = 8), steps used in the transmission of digital terrestrial television DVB-T. The system model is proposed, a brief description of the VI is used and the performance curves of bit error rates are presented in an AWGN channel for each modulation schemes modeled.